Papua New Guinea Trade Facilitation Challenges for Women Traders and Freight Forwarders : Survey Findings and Recommendations - World Bank (World Bank, Washington, DC, 2021)
Trade is widely recognized to be an engine of growth that creates jobs, reduces poverty, and increases economic opportunity. There is a global lack of data on how trade facilitation interventions impact traders by gender at the firm level. This lack of data may also reinforce the bias against women in trade policy making. To help fill the data gap with an aim to better inform future design and implementation of trade facilitation projects, the World Bank Group (WBG) has collected data through a survey on cross-border trade challenges faced by both women and men at the firm level in the Pacific Islands region. This note presents findings of the survey work in Papua New Guinea (PNG). The survey has highlighted several areas that could be addressed by the government of PNG to improve the trade facilitation environment in PNG. Specific emphasis in the recommendations has been made to address asymmetric gender barriers that occur in cross-border trade. This report presents the results of a survey undertaken in Papua New Guinea from February to March 2020 with the intention to identify specific challenges cross-border traders are facing related to trade facilitation at the firm level.